Integrating LEGO-Based Constructive Media to Foster Patience Character Development in Early Childhood: A Study at TK Miftahul Ulum 27 Pamekasan - Shofiyana Shofiyana; Dewi Pusparini (Universitas Islam Lamongan, 2026)
This study examines the effectiveness of LEGO-based constructive media in fostering patience as a core dimension of self-regulation among early childhood learners at TK Miftahul Ulum 27 Pamekasan. Grounded in constructivist and socio-cultural learning theories, the research employs a qualitative case study approach to explore how experiential, play-based learning environments facilitate character development. Data were collected through observations, in-depth interviews, and documentation, involving teachers, school leaders, parents, and children aged 5–6 years. The findings reveal that LEGO-based learning significantly enhances children’s ability to regulate emotions, delay gratification, persist in tasks, and engage in cooperative social interactions. The implementation process, when systematically designed and supported by effective teacher facilitation, enables children to internalize patience through meaningful and repeated learning experiences. However, the effectiveness of the approach is influenced by multidimensional factors, including individual developmental differences, institutional support, and family involvement. The study further proposes a LEGO-based constructive learning model comprising instructional design, implementation processes, and character outcomes. This model highlights the importance of integrating play-based strategies with character education to achieve holistic development. The findings contribute to the advancement of early childhood pedagogy by emphasizing that character formation is most effective when embedded in authentic, experiential learning contexts.